2011
DOI: 10.3109/10428194.2011.576791
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stromal cells protect myeloma cells from bortezomib induced apoptosis by suppressing microRNA-15a expression

Abstract: Despite unsurpassed anti-tumor activity of bortezomib for multiple myeloma (MM), drug resistance has emerged as a challenge, especially when MM cells adhere to the stroma. This study aimed to determine whether bone marrow stromal cells (BMSCs) have a role in the development of chemoresistance in MM. Our data demonstrate that the secretion of interleukin-6 (IL-6), vascular endothelial growth factor (VEGF), and cell-to-cell contact with microenvironment-derived stromal cells from patients with multiple myeloma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 23 publications
2
92
0
Order By: Relevance
“…In particular, several of the identified downregulated miRNAs in association with the loss of the corresponding genomic loci have already been linked to cancer as having a tumor suppressor role: this is the case of miR-22 (22,23), miR-30e and miR-30c (24), miR-331-3p (25), and miR-342-3p (26). The downregulation of miR-15a in patients carrying chromosome 13 deletion is of particular importance given the frequency of this genomic lesion in pPCL and the experimental evidence that it may act as a tumor suppressor in malignant plasma cells (27,28). As regards miR-17-92 cluster, copy number of chromosome 13 was unlikely to be the only factor affecting its expression in our pPCL cohort; in fact we found that some miRNAs belonging to the cluster were significantly overexpressed in pPCL compared with multiple myeloma cases independently of their CN status.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, several of the identified downregulated miRNAs in association with the loss of the corresponding genomic loci have already been linked to cancer as having a tumor suppressor role: this is the case of miR-22 (22,23), miR-30e and miR-30c (24), miR-331-3p (25), and miR-342-3p (26). The downregulation of miR-15a in patients carrying chromosome 13 deletion is of particular importance given the frequency of this genomic lesion in pPCL and the experimental evidence that it may act as a tumor suppressor in malignant plasma cells (27,28). As regards miR-17-92 cluster, copy number of chromosome 13 was unlikely to be the only factor affecting its expression in our pPCL cohort; in fact we found that some miRNAs belonging to the cluster were significantly overexpressed in pPCL compared with multiple myeloma cases independently of their CN status.…”
Section: Discussionmentioning
confidence: 99%
“…BMSCs provided survival support and protected myeloma cells from bortezomib induced apoptosis via suppressing miR-15a/-16 expression. Notably, IL-6 secreted by MM-BMSCs decreased the expression of miR-15a/-16 in myeloma cells in a time and dose-dependent manner [131,132]. Another miRNA, known as miR-33b, has been shown to play an important role in the anti-MM function of MLN2238, a novel orally active proteasome inhibitor [133].…”
Section: Mirnas Regulate the Tumor Microenvironmentmentioning
confidence: 96%
“…Thus, multitargeted drugs such as TG02 may offer an important new therapeutic approach. For instance, multiple myeloma cells nurtured by cytokines derived from bone marrow stroma show increased proliferation and resistance (29), but inhibition of the TG02 target kinases can reverse this process. Indeed, cytokine-activated ERK5 was affected in MM1S cells by TG02 suggesting that inhibition of ERK5 contributes to the ability of TG02 to overcome the protective effects of the bone marrow niche in multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%